PENGEMBANGAN INDUSTRI CPO DAN PROSPEKNYA DIPASAR UNI EROPA - Asnur Elly Samah; Yati Nuryati (Buletin Ilmiah Litbang Perdagangan, 2009)
Europe Union (UE) is a large market that has opportunities for Indonesia Crude Palm Oil (CPO) export. Share export of Indonesia CPO in UE Market is 41,2 percent. This number more consider than other development countries and other big countries, for example United States, Japan and Canada. Demand of CPO in UE market shows increasing analogous with utilization biodiesel as energy alternative. The objective of this paper to: (1) Describe production and potency of Indonesia CPO performance and (2) analisys of prospective of CPO Product performance in UE  marked related with uses oils and biodisel . The analisys uses  descriptive  and hold winters  approach method to forecast, the time series data from 1990 to 2008. Main Result of this research are (1) developing of CPO product in the future still prospective with increasing oils consumption, oils world and utilization biodisel energy. (2) share  export Indonesia CPO in International market at 42 percent and tends to increase in five years latest, and (3) the projection Indonesia CPO Export in 2011 achive about 12 to 18 percent. The study suggests that government policy focused to developt of CPO and their derivative product to support export market diversiification and strengthened domestic market with development industry from off farm to absorp excess suplay CPO domestic.